Deformable Registration of Glioma Images Using EM Algorithm and Diffusion Reaction Modeling - Gooya, Ali (2010)
This paper investigates the problem of atlas registration of brain images with gliomas. Multi-parametric imaging modalities (T1, T1-CE, T2, and FLAIR) are first utilized for segmentations of different tissues, and to compute the posterior probability map (PBM) of membership to each tissue class, using supervised learning. Similar maps are generated in the initially normal atlas, by modeling the tumor growth, using reaction-diffusion equation. Deformable registration using a demons-like algorithm is used to register the patient images with the tumor bearing atlas. Joint estimation of the simulated tumor parameters (e.g. location, mass effect and degree of infiltration), and the spatial transformation is achieved by maximization of the log-likelihood of observation. An Expectation-Maximization algorithm is used in registration process to estimate the spatial transformation and other parameters related to tumor simulation are optimized through Asynchronous Parallel Pattern Search (APPSPACK). The proposed method has been evaluated on five simulated data sets created by Statistically Simulated Deformations (SSD), and fifteen real multichannel glioma data sets. The performance has been evaluated both quantitatively and qualitatively, and the results have been compared to ORBIT, an alternative method solving a similar problem. The results show that our method outperforms ORBIT, and the warped templates have better similarity to patient images.